Pomegranate Juices: Analytical and Bio-Toxicological Comparison of Pasteurization and High-Pressure Processing in the Development of Healthy Products - Francesco Cairone; Stefania Cesa; Irene Arpante; Simonetta Cristina Di Simone; Alejandro Han Mendez; Claudio Ferrante; Luigi Menghini; Antonello Filippi; Caterina Fraschetti; Gokhan Zengin; Simone Carradori; Marialucia Gallorini; et al. (Foods)
Two different produced and packaged commercial typologies of pomegranate juice were analyzed for their physicochemical, nutritional, and biological properties. The effects of classical pasteurization (PJ) and high-pressure processing (HP), applied during the productive cycle, were evaluated through several advanced analytical methods, such as CIEL*a*b* colorimetry, HPLC-DAD, DI-ESI-MS and MS/MS, and NMR analyses. Moreover, the exerted biological activity of the two pomegranate juices was monitored through Total Phenolic and Total Flavonoid Contents, antiradical, antioxidant and chelating activity. The potential inhibition of key enzymes of degenerative processes (cholinesterases, tyrosinase) and diabetes (amylase, glucosidase), the allelopathy toward Cichorium intybus, Dicondra repens, and Diplotaxis tenuifolia, and the in vivo toxicity on brine shrimp were also evaluated. The two different applied processing techniques analyzed impacted the bioactive compound’s preservation differently, modifying the phytocomplex profile. HP significantly degrades punicalins and punicalagins, better preserving anthocyanins, if compared to PJ’s impact. Sensory qualities, antioxidant activity, enzymatic inhibition, and ecotoxicological potential were differently impacted by the two applied processes. The obtained results can be beneficial for finding the optimal processing conditions that balance microbial safety with nutritional value preservation, contributing to the development of healthy pomegranate juice products.